FMEA-Failure Mode and Effect Analysis (Research Bulletins of the Faculty of Economic Sciences, 2021)
FMEA Failure Mode and effect Analysis or FMECA{ Failure Mode andcriticality analysis} consist on the analytical establishment of casual links in the processof potential failures creation and on including in an analysis the critical factor { riskfactor } the aim of the analyses is consequent and systematic identification of potentialproduct\process failures and the elimination or minimizing the risk connected with it.The article presents not only the aims of and reasons for applying FMEA, but alsostages of the analysis and its applications
Keywords: FMEA method, quality